1998
DOI: 10.1126/science.279.5351.717
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Cellulose Biosynthesis in Arabidopsis

Abstract: Cellulose, an abundant, crystalline polysaccharide, is central to plant morphogenesis and to many industries. Chemical and ultrastructural analyses together with map-based cloning indicate that the RSW1 locus of Arabidopsis encodes the catalytic subunit of cellulose synthase. The cloned gene complements the rsw1 mutant whose temperature-sensitive allele is changed in one amino acid. The mutant allele causes a specific reduction in cellulose synthesis, accumulation of noncrystalline beta-1,4-glucan, disassembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
648
1
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(686 citation statements)
references
References 26 publications
30
648
1
7
Order By: Relevance
“…(ixr1) and CESA6 (prc, ixr2) genes in most tissues is also compatible with the observations from genetic studies that these genes are involved in primary wall synthesis throughout the plants (also see below) (Arioli et al 1998;Fagard et al 2001;Scheible et al 2001). A CESA10::GUS promoter fusion indicates that CESA10 is expressed at the base of rosette leaves in Arabidopsis, which correlates with the very weak expression of the gene on the gene chips (Doblin et al 2002).…”
Section: Resultssupporting
confidence: 66%
“…(ixr1) and CESA6 (prc, ixr2) genes in most tissues is also compatible with the observations from genetic studies that these genes are involved in primary wall synthesis throughout the plants (also see below) (Arioli et al 1998;Fagard et al 2001;Scheible et al 2001). A CESA10::GUS promoter fusion indicates that CESA10 is expressed at the base of rosette leaves in Arabidopsis, which correlates with the very weak expression of the gene on the gene chips (Doblin et al 2002).…”
Section: Resultssupporting
confidence: 66%
“…[6][7][8][9] We recently showed that in Arabidopsis thaliana cellulose-deficient thanatos and pom2-4 mutants, of AtCesA3 and AtCSI1 respectively, suppression of cell expansion results in cortical microtubule reorientation in the fast elongation zone. 10 As both genes are involved in cellulose synthesis in primary cell walls, we examined the orientation of microtubules in 2 additional primary wall-related mutants, radially swollen1 (rsw1) 11,12 and procuste1 (prc1) 13 of AtCesA1 and AtCesA6, respectively.…”
Section: Cortical Microtubule Patterning Is Aberrant In the Fast Elonmentioning
confidence: 99%
“…On the contrary, in the meristematic and transition zones cortical microtubules exhibit transverse orientation (black lines) reminiscent of the pattern in wild-type roots. The mutants are: pom2-4 of Cellulose Synthase Interacting1 protein (CSI1), 3 prc1 (procuste1 of CesA6), 13 rsw1 (radially swollen1 of CesA1), 11,12 and than (thanatos of CesA3). 19 …”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…(ii) Proper assembly of CelS depends on protein encoded by AtCesA1: To demonstrate that rosettes are made up of intact CESAs, the temperature-sensitive mutant rsw1 was analyzed (Arioli et al, 1998). It displayed disassembly of CelS (or rosettes) in the plasma membrane, altered cellulose crystallinity (or production of non-crystalline cellulose), and interrupted morphogenesis.…”
Section: Cels Is Composed Of Cesa Isoforms That Are Encoded By Cesa Gmentioning
confidence: 99%
“…It was proposed that the rsw1 mutant allele interrupts assembly of glucan chains into microfibrils. In the mutant, at the restrictive temperature, CelS is not properly assembled suggesting that the proper assembly of CelS depends on the presence of wild-type AtCesA1 (Arioli et al, 1998).…”
Section: Cels Is Composed Of Cesa Isoforms That Are Encoded By Cesa Gmentioning
confidence: 99%